Aedes aegypti lachesin protein binds to the domain III of envelop protein of Dengue virus‐2 and inhibits viral replication. (20th March 2020) - Rana, Vipin S.; Popli, Sonam; Saurav, Gunjan K.; Yadav, Karuna; Kumar, Ankit; Sunil, Sujatha; Kumar, Narendra; Singh, Om P.; Natarajan, Krishnamurthy; Rajagopal, Raman
Abstract: Dengue virus (DENV) comprises of four serotypes (DENV‐1 to ‐4) and is medically one of the most important arboviruses (arthropod‐borne virus). DENV infection is a major human health burden and is transmitted between humans by the insect vector, Aedes aegypti . Ae. aegypti ingests DENV while feeding on infected humans, which traverses through its gut, haemolymph and salivary glands of the mosquito before being injected into a healthy human. During this process of transmission, DENV must interact with many proteins of the insect vector, which are important for its successful transmission. Our study focused on the identification and characterisation of interacting protein partners in Ae. aegypti to DENV. Since domain III (DIII) of envelope protein (E) is exposed on the virion surface and is involved in virus entry into various cells, we performed phage display library screening against domain III of the envelope protein (EDIII) of DENV‐2. A peptide sequence showing similarity to lachesin protein was found interacting with EDIII. The lachesin protein was cloned, heterologously expressed, purified and used for in vitro interaction studies. Lachesin protein interacted with EDIII and also with DENV. Further, lachesin protein was localised in neuronal cells of different organs of Ae. aegypti by confocal microscopy. Blocking of lachesin protein in Ae. aegypti with anti‐lachesin antibody resulted in a significant reduction in DENV replication.